Pemberdayaan Kader Posyandu dalam Meningkatkan Validitas dan Akurasi Data Berbasis Digital di Kamboja 5 Gedangan : Pengabdian - Fidela Berliani Prasaja Putri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The main issue frequently encountered in the implementation of Posyandu (Integrated Health Post) activities is the low accuracy and validity of toddler health data due to unsystematic manual recording and the limited data management skills of Posyandu cadres. Inaccurate data has the potential to hinder decision-making in early childhood health interventions. Therefore, this community service initiative aims to empower Posyandu cadres through training and mentoring in the use of a simple digital application based on Microsoft Excel. The activity was focused at Posyandu Kamboja 5, located in the Gedangan Permai residential area, which is a densely populated region with a relatively high number of toddlers. The implementation methods included needs analysis, technical training on Excel usage, simulation of toddler health data entry, and evaluation of cadres' competencies before and after the training. The results of the program indicated a significant improvement in the cadres' ability to manage and analyze health data digitally. Furthermore, the use of digital formats accelerated the data recapitulation process and enhanced the accuracy of the information reported to the local community health center (Puskesmas).